2021
DOI: 10.1016/j.foodqual.2020.104085
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fishery and aquaculture products consumption at home in the EU28

Abstract: The European Union (EU) is the world's largest market for fishery and aquaculture products (FAPs) in nominal terms. Given the importance of these products, EU authorities and policy-makers are continuously monitoring consumer preferences and attitudes, analysing whether or not the implementation of EU policies and regulations improves the market conditions. For example, the Eurobarometer (European Union, 2018a) surveyed 27,732 EU residents including a specific module to analyse the fishery and aquaculture EU m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 72 publications
6
27
1
Order By: Relevance
“…Recent results of at-home fishery and aquaculture products consumption among consumers from 28 EU countries confirmed that one of the main reasons for buying or eating fish and aquaculture products is because they are healthy, while the biggest barrier to greater consumption is a lack of understanding of the information labelled on fishery and aquaculture products [ 45 ]. Health consciousness and dietary habits of consumers are closely related to frequency of physical activity [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent results of at-home fishery and aquaculture products consumption among consumers from 28 EU countries confirmed that one of the main reasons for buying or eating fish and aquaculture products is because they are healthy, while the biggest barrier to greater consumption is a lack of understanding of the information labelled on fishery and aquaculture products [ 45 ]. Health consciousness and dietary habits of consumers are closely related to frequency of physical activity [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to take cultural perceptions into account, as consumer attitudes towards seafood safety are often conflated with perceptions of sustainability, quality, and traceability [86]. Certain European consumers seem to be willing to pay more for "fresh" seafood compared to frozen seafood [72,87,88]. Additionally, while frozen seafood is commonly sold in most marketplaces, in some countries, such as China, fresh seafood is highly preferred, ideally purchased "live" compared to other product forms (e.g., frozen or canned) [79].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of consumers in the European Union, Cantillo et al [88] found that consumers who do not understand all the information provided on seafood products tend to consume less seafood. This indicates an opportunity to increase consumption by providing clearer information about the product.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations